Compensation for oil pollution damage - Matyugina E. G. Eleonora Grigorievna; Glyzina T. S. Tatiana Svyatoslavovna; Kolbysheva Yu. V. Yuliya Vladimirovna; Klyuchnikov A. S.; Vusovich O. V. (Petroleum Engineering Economics. Mining Law, 2015)
Title screen